PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PEMBUATAN ROLL ON AROMATERAPI DARI MINYAK SEREH SEBAGAI ANTI REPELLENT - Yumni, Gharsina Ghaisani; Hidayati, Devi Nisa; K. M., Dewi Andini (Universitas Mataram, 2024)
Dengue fever (DF) is a global health problem. The epidemiology of dengue fever in Indonesia varies but continues to increase. Dengue fever itself is caused by the Aedes aegypti (Linn.) mosquito. Indonesia's tropical geographical location provides conditions that support the breeding of disease-carrying mosquitoes. This demonstrates the urgency with which disease-carrying mosquito eradication must be carried out. Currently, mosquito control strategies rely on the use of chemical drugs to control mosquitoes, which often cause side effects. Therefore, many mosquito repellents have been developed based on natural ingredients. Cymbopogon nardus, the plant that yields citronella essential oil, is one of them. The purpose of this PkM project is to increase knowledge regarding the benefits of citronella oil. In addition, it also improves the skills of participants to produce citronella oil as an anti-repellent. This training method is a combination of lectures, demonstrations, and practical actions. Participants will be given counseling regarding the benefits of citronella oil for health. The making of roll-on preparations begins with watching tutorials and live demonstrations by the team which are then followed by the participants. The results of this activity showed an increase in participants' knowledge and skills in making lemongrass aromatherapy roll-on preparations. This can be seen in the PkM product in the form of a roll-on aromatherapy preparation that has a distinctive lemongrass aroma, warm and stable at room temperature. Participants can also plan to make roll-on preparations using other essential oils. The knowledge gained is expected to be developed by participants as entrepreneurial capital. The community service activities were carried out smoothly and according to target. The PkM team succeeded in increasing the knowledge and skills of the participants through PkM activities.